Hungry girl simply comfort : feel-good favorites for your slow cooker & air fryer - Lillien, Lisa (St. Martin's Griffin, 2022)
"From the #1 New York Times bestseller author Lisa Lillien, Hungry Girl Simply Comfort provides all natural recipes for your air fryer, slow cooker and more! Finally... An entire Hungry Girl cookbook of comfort food recipes you make in an air fryer or slow cooker! This book takes the delicious decadence of nostalgic and comforting favorites and combines it with the convenience of cooking in your favorite countertop appliances. Get ready for... * crispy air-fried appetizers * mouthwatering meatloaves * hearty stews * slow-cooker casseroles * dump cook desserts ... and so much more! Hungry Girl Simply Comfort is a must for anyone who loves comfort food, convenience cooking, natural ingredients and saving some calories while they're at it!"--